LEARNING PROGRAM EDUCATION IN VOCATIONAL HIGH SCHOOLS: AN EVALUATION INSTRUMENT’S VALIDITY - Qothrun Nada Ma'ruf Batubara; Diah Indah Pratiwi; Siti Maisyarah Hasibuan (STKIP PGRI Situbondo, 2025)
This study focuses on the development and validation of an evaluation instrument for the Industrial Clothing Making learning program in vocational high schools. With the growing importance of vocational education in preparing students for industry-specific careers, it is essential to ensure that the evaluation tools used are both valid and reliable. The primary objective of this research was to create an instrument that accurately assesses the effectiveness of the Industrial Clothing Making program, addressing existing gaps in evaluation practices. The research methodology involved a comprehensive review of existing evaluation instruments, consultations with educational experts and industry professionals, and the development of an initial instrument consisting of 80 items. The instrument underwent a rigorous validation process that included expert reviews, pilot testing, and statistical analysis using Aiken's V to assess content validity. The results revealed that 70 of the original 80 items were deemed valid by experts, effectively covering the essential competencies and knowledge areas of the Industrial Clothing Making program. Ten items were identified as inadequate and were subsequently replaced to enhance the instrument's overall validity. The use of Aiken's V further confirmed the validity of the instrument, with each item in the validation questionnaire achieving a score above 0.8, indicating a high level of agreement among experts.